Isovalent AgIII/AgIII, AgII/AgII, Mixed‐Valent AgII/AgIII, and Corrolato‐Based Mixed‐Valency in β, β′‐Linked [Biscorrolato‐silver]n Complexes. Issue 56 (7th September 2017) - Patra, Bratati; Sobottka, Sebastian; Sinha, Woormileela; Sarkar, Biprajit; Kar, Sanjib
Abstract: Mixed‐valent compounds are fascinating entities that are useful as models for investigating electron‐transfer reactions, and find use in a host of biologically relevant redox processes. Though the bio‐relevant metal copper is well established in mixed‐valent chemistry, the Ag II /Ag III mixed‐valent combination of its higher congener in a molecular complex has rarely been reported before. This work reports the synthesis of a new β, β′‐linked bis{corrolato‐silver(III)} complex and its characterization in five different redox states. A combination of electrochemistry, spectroelectrochemistry, and DFT calculations point to the existence of a mixed‐valent Ag II /Ag III and an isovalent Ag II /Ag II form. Additionally, characterization of the Ag III /Ag III form and ligand‐based corrolato‐centered mixed‐valency is presented as well. These results thus open new avenues for bis‐corrolato ligands and for mixed‐valency in disilver compounds. Abstract : Silver lining : Electrochemical, spectroelectrochemical, and DFT calculations point to the existence of Ag II /Ag II, Ag II /Ag III, Ag III /Ag III, and corrolato‐bridged mixed valency in a dicorrolato‐based disilver complex.